More human than human? Artificial intelligence in the archive. Issue 2 (4th May 2019) - Rolan, Gregory; Humphries, Glen; Jeffrey, Lisa; Samaras, Evanthia; Antsoupova, Tatiana; Stuart, Katharine
ABSTRACT: Not a day appears to go by without breaking news of some Artificial Intelligence (AI) advance that seemingly has the potential to transform our lives. As recordkeeping professionals, we can very well ask, 'What about us?' Where is the AI or automation to help us with our classification, appraisal and disposal work? If we are to meet the challenges of managing records in the digital age, such technology – together with appropriate skills and knowledge – will be necessary. How can AI automate our digital recordkeeping and archive work? In this article, the authors provide a snapshot of the practice of AI in Australian recordkeeping. What is the reality versus the hype of such technology, and what is actually being done now? In answering these questions, they first provide a brief introduction into AI techniques and their characteristics in relation to recordkeeping work. They then introduce four case studies from Australian archival and government institutions that have embarked on AI initiatives. In each case, they provide an overview of the project in terms of requirements, activities to date, outcomes and futures. The article concludes with a discussion of the lessons learnt, issues and implications of AI in the archive.